Coulteria delgadoana (Leguminosae, Caesalpinioideae), a new species from the Western Río Balsas Depression, Mexico - Sotuyo Vázquez, Jeny Solange; Contreras-Jiménez, José Luis (Instituto de Ecología, A.C., 2021)
Background and Aims: In Mexico, Coulteria is a morphologically diverse genus, having many endemic species in the country. Despite its diversity, species delimitation and circumscription are not fully documented. Botanical explorations in central Mexico during the last 25 years have resulted in the discovery of several new legume taxa in the Río Balsas Depression. A new species of Coulteria from the Western Río Balsas Depression is here described and illustrated.Methods: During fieldwork, morphological studies and electron microscopy analysis of the already species described of Coulteria, we detected a new species in the Infiernillo area of Guerrero and Michoacán, Mexico. For the new species, we estimated its conservation status based on extent of occurrence (EOO) and its area of occupancy (AOO) using the GeoCAT software, applying the categories and criteria of the IUCN Red List.Key results: Coulteria delgadoana, a new species of Caesalpinioideae endemic to the seasonally dry forest of Guerrero and Michoacán (Western Río Balsas Depression), Mexico, is described and illustrated based on morphological evidence. Coulteria delgadoana has long male inflorescences up to 15 cm long, small flowers, leaves with glabrous leaflets and prominent reticulate venation, and a glabrous chestnut brown fruit with purplish tints. Based on IUCN criteria, we suggest an Endangered (EN) category of the species.Conclusions: Morphological characters of the new species C. delgadoana, suggest that it is similar to C. glabra, a species from Colima and Jalisco. The long size of the male inflorescence has not been observed in other Coulteria species. Coulteria delgadoana shares its distribution area with C. lewisii in Infiernillo.